SharePoint 2007 User’s Guide : Learning Microsoft’s Collaboration and Productivity Platform - Bates, Seth (Apress, 2013)
The chapters in this book are organized into two groups. Chapters 1 through 9 offer the fundamental knowledge of SharePoint 2007 that users need to successfully utilize the capabilities provided by the technology. This group can be used as an end-to-end reference guide, allowing you to easily look up specific SharePoint topics, and it includes step-by-step instructions, figures, tables, and examples. The capabilities described in these chapters are important and act as the building blocks for the solutions described in the second group of chapters.